(untitled) - MIMS VietNam (Tp. HCM, 1998)
This book offers the latest information on drugs available in VietNam. Brief but essential information is compiled in monographs listed by therapeutic class. There is an extensive cross-referencing so you can also look up drug information by brand name, generic name and indications, aside from therapeutic class
Keywords: drug therapy